2020
DOI: 10.1099/mic.0.000908
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an alcohol dehydrogenase gene in a heterotrophic bacterium induces carbon dioxide-dependent high-yield growth under oligotrophic conditions

Abstract: Sphingobium japonicum strain UT26, whose γ-hexachlorocyclohexane-degrading ability has been studied in detail, is a typical aerobic and heterotrophic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Furthermore, DNA microarray analysis revealed that two genes, aldA and mnoA, encoding NAD-ALDH and NDMA-MDH, respectively, were strongly expressed under oligotrophic conditions [6]. All the super oligotrophs that we isolated previously belonged to the genera Rhodococcus and Streptomyces [1,5], and Nagata found that a transposon-induced mutant of Sphingobium japonicum UT26 showed oligotrophic features, and a Zn-dependent alcohol dehydrogenase was essential for oligotrophic growth [7].…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, DNA microarray analysis revealed that two genes, aldA and mnoA, encoding NAD-ALDH and NDMA-MDH, respectively, were strongly expressed under oligotrophic conditions [6]. All the super oligotrophs that we isolated previously belonged to the genera Rhodococcus and Streptomyces [1,5], and Nagata found that a transposon-induced mutant of Sphingobium japonicum UT26 showed oligotrophic features, and a Zn-dependent alcohol dehydrogenase was essential for oligotrophic growth [7].…”
Section: Introductionmentioning
confidence: 82%